The Relavansi Etnosains pada Permainan Tradisional Gasing dalam Materi IPA : Relevance of Ethnoscience to the Traditional Game of Spinning Tops in Science Material - Martiana, Rina; Purnama, Dunia; Osi, Zaena Sultona; Maharani, Bintang; Mahrus, Mahrus; Andayani, Yayuk (Yayasan Arfah Bin Haji Muhammad Saleh, 2025)
This study aims to identify the relevance of ethnoscience in the traditional spinning top game in East Lombok to science learning materials, especially the concept of force and motion. The method used is descriptive qualitative with data collection techniques in the form of observation, interviews, and literature studies. Observations were conducted in Masbagik Village, East Lombok, involving spinning top players, spinning top makers, traditional leaders, and science teachers. The results of the study indicate that the spinning top game contains scientific principles such as torque, moment of inertia, center of mass, rotational energy, and mechanical properties of materials that are in accordance with science materials in junior high schools. In addition, this game also teaches character values ​​such as discipline, responsibility, and cooperation. Thus, the spinning top game has great potential to be integrated into ethnoscience-based science learning as an effort to preserve culture while increasing understanding of science concepts contextually.